Pengujian Implementasi Disaster Recovery Menggunakan Ansible - Miftahul Ulum; Muhammad Agung Nugroho; Edi Iskandar; Sudarmanto Sudarmanto (The Indonesian Journal of Computer Science Research, 2023)
Cloud-based technology is a technology that constructs the internet as a central server for managing data and also user applications. Because the smooth process of processing data in a company/organization depends on IT infrastructure, data protection and recovery become essential, especially in damage or natural disasters. Files or data stored and processed by a company/organization will increase in size so that centralized and organized data storage is needed, namely by managing data in a data centre. The data backed up will be stored in a replica of the main data centre; the replica can act as an alternative if the primary data centre is undergoing maintenance or maintenance (down). Consequently, we need a system that can overcome obstacles when the data centre is down and requires a new data centre that is fast and reliable to handle the backup with ansible